2021
DOI: 10.1200/jco.20.02342
|View full text |Cite
|
Sign up to set email alerts
|

Eprenetapopt Plus Azacitidine in TP53-Mutated Myelodysplastic Syndromes and Acute Myeloid Leukemia: A Phase II Study by the Groupe Francophone des Myélodysplasies (GFM)

Abstract: PURPOSE TP53-mutated ( TP53m) myelodysplastic syndromes (MDS) and acute myeloid leukemia (AML) have very poor outcome irrespective of the treatment received, including 40% responses (20% complete remission [CR]) with azacitidine (AZA) alone, short response duration, and a median overall survival (OS) of approximately 6 months. Eprenetapopt (APR-246), a novel first-in-class drug, leads to p53 protein reconformation and reactivates its proapoptotic and cell-cycle arrest functions. PATIENTS AND METHODS This phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
131
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 201 publications
(145 citation statements)
references
References 25 publications
14
131
0
Order By: Relevance
“…Toxicity was acceptable, with the most common grade 3 or more AEs being febrile neutropenia and cytopenias. The results of this study are consistent with the phase II study by de GFM evaluating the safety and efficacy of eprenetapopt in combination with AZA in untreated high or very high TP53 mutated MDS and AML patients [ 76 ]. These studies have led to the ongoing pivotal phase III, multicenter, randomized study of eprenetapopt combined with AZA versus AZA alone in patients with TP53 -mutant MDS (NCT03745716).…”
Section: High-risk Mds (Hr-mds)supporting
confidence: 89%
“…Toxicity was acceptable, with the most common grade 3 or more AEs being febrile neutropenia and cytopenias. The results of this study are consistent with the phase II study by de GFM evaluating the safety and efficacy of eprenetapopt in combination with AZA in untreated high or very high TP53 mutated MDS and AML patients [ 76 ]. These studies have led to the ongoing pivotal phase III, multicenter, randomized study of eprenetapopt combined with AZA versus AZA alone in patients with TP53 -mutant MDS (NCT03745716).…”
Section: High-risk Mds (Hr-mds)supporting
confidence: 89%
“…This is probably because in regions other than North America, healthcare data are often scattered in different and heterogeneous databases, so that the performing studies on rare events that requires information from different healthcare settings, as in the case of lung cancer, remains a challenge [ 56 ]. Moreover, the approval of new anticancer medication in Europe is often delayed compared to the US [ 57 ], possibly contributing to the higher number of studies from the US included in this review compared to those using European Union (EU) data.…”
Section: Discussionmentioning
confidence: 99%
“…Several ongoing clinical trials are testing the safety and efficacy of APR-246 for different cancer types (NCT03931291, NCT04214860, NCT04383938, NCT03745716, NCT04419389, NCT03588078, and NCT03072043 at ClinicalTrials.gov (accessed on 1 July 2021)). The latest result of the phase 2 trial (NCT03072043) showed combination treatment with eprenetapopt (APR-246) and azacitidine is well tolerated yielding high rates of clinical response and molecular remissions in patients with TP53-mutant myelodysplastic syndromes [88,89]. KSS-9 is a piperlongumine derivative with the insertion of combretastatin A4 at the C-7 position.…”
Section: Reactivating Wild-type P53 Functionmentioning
confidence: 99%